Development of LSCF cathode perovskites for solid oxide fuel cell / Nur Syuhada Mat Radzi, Ammar Mohd Akhir and Norhasyimi Rahmat - Mat Radzi, Nur Syuhada; Mohd Akhir, Ammar; Rahmat, Norhasyimi (Universiti Teknologi MARA Shah Alam, 2022)
Solid oxide fuel cell (SOFC) is a technology that converts chemical energy to electrical energy which is used to generate powers such as turbines. The cathode in SOFC is developed with the material consisting of lanthanum strontium cobalt ferrite (LSCF) with good mixed ionic electronic conductivity (MIEC) properties. The LSCF pellet is prepared by an annealing temperature in a furnace within the temperature of 600 to 900 ℃. With these temperatures, it is crucial to investigate the annealing temperature effect of the LSCF crystalline structure, morphological studies, and its electrical conductivity. The pellet contains LSCF undergoes X-ray diffraction (XRD) for crystalline structure and electrical impedance spectroscopy (EIS) for electrical performances and conductivity. The crystalline structure tested with XRD shows a similar diffraction peak even with the increasing temperature of annealing. As the annealing temperature gets higher, the main peak becomes smoother. As for the lowest annealing temperature of 600 ℃, the diffraction peaks seem unstable compared to 700 ℃ and above. This suggests that LSCF has a stability of structure at a high operating temperature of SOFC. The electrical impedance of the fabricated LSCF pellet is at the lowest annealing temperature of 600 ℃ with a value of 0.00554 Ω·cm. By the objective to lower the operating temperature of SOFC, the LSCF produces a small impedance and electrical conductivity. Also, the LSCF compound has the best structure stability at a high temperature above 700 ℃.